Pyrite-Goethite Alteration in Supergene Oxidation Processes in Till: Elemental Distribution and Evaluation of Goethite Usability as a Fingerprinting Tool for Vectoring Mineral Deposits - Atte Taivalkoski; Jukka-Pekka Ranta; Pertti Sarala; Marko Moilanen; Paavo Nikkola; Tapio Soukka (Minerals, 2024)
In the formerly glaciated terrains in the northern hemisphere and countries such as Finland, till is the most common sediment covering the bedrock. Specifically, indicator or heavy mineral studies utilising till as a vector for mineral deposits undercover have been successful. The pyrite trace-element composition from in situ mineral analyses has been shown to be an effective discriminator between different mineral deposit types, and this has led to research using heavy mineral pyrite in till to identify potential mineral deposits in a given area. However, pyrite is easily oxidised in till beds, and thus, alternative methods should be considered. Goethite pseudomorphs are more commonly found in the till sediments as remnants after pyrite oxidation. This study evaluates trace element compositions of goethitised pyrite recovered in the till beds from central Lapland in northern Finland. Intra-grain trace-elemental variations gathered using laser-ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) between the intact pyrite core and oxidised rim demonstrated complex dynamics and variations between different trace-element values. For example, Cu, V and Mn exhibited elevated trace-element values in the goethite rim compared to the pyrite core. However, elemental ratios such as Ni/As and Co/Ni remain stable between the pyrite core and oxidised rim. Therefore, these ratios have the potential to be used as a discriminating tool between the pyrite core and oxidised rim. In addition, nanoscale variabilities using focused ion beam (FIB) and transmission electron microscopy (TEM) were utilised to inspect possible nano inclusions within the studied heavy mineral grain. The FIB and TEM studies revealed a nanocrystalline pyrite nodule observation within the goethite rim.